Ways to Use Text Issues When Cultivating Students ' Thinking Skills - Rakhmonkulova Nafisa Khasanovna; Mirzanazarova Shukurona Avazbek qizi (International Journal on Integrated Education, 2022)
Solving textual issues the formation of excellent mathematical concepts in children first of all is important in the development of students ' thinking skills, along with the assimilation of their theoretical knowledge, which is determined in the program. For example: if we want to form a correct understanding of addition in students, for this it is necessary that children solve a sufficient number of simple issues related to finding the sum, almost every time following the action of combining sets. For example: the following issue is given.